(untitled) (Philological Studies, 2019)
In Russian and Komi-Permyak folklore legends about the treasures, there are rare motives where the rooster appears. The article is devoted to two motives with difficult task for a person who wants to take a hoard (to harness 12 roosters; to hit the bell faster than a rooster will sing). These motives are analyzed in the context of other folk stories about treasures. It shows the functions of the rooster in this group of oral narratives: this bird is the guard of the treasure; it is mentioned in the so-called “formula of the impossible”; it is sacrificed for the sake of receiving wealth; it helps or hinders to find a treasure; it is a personification of hoard.